THE SEMANTIC – STRUCTURAL PRIORITIES OF ICT TERMINOLOGY - Mirodilova, Nargiza (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article is devoted to the study of the structural and semantic characteristics of computer terminology in English. The peculiarities of the word-formation process and the functioning of English computer terms are analysed. Moreover, as the technology is coming into every sphere of the life, the terminology is also should be obtained each branch of science eventually. This importance of ICT terminology is discussed widely.